2021
DOI: 10.1038/s41598-021-85340-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical severity and epidemiological spectrum between coronavirus disease 2019 and influenza in children

Abstract: Data on the novel coronavirus disease 2019 (COVID-19) in children are limited, and studies from Europe are scarce. We analyzed the clinical severity and epidemiologic aspects of COVID-19 in consecutive children aged 0–18 years, referred with a suspicion of COVID-19 between February 1, and April 15, 2020. RT-PCR on a nasopharyngeal swab was used to confirm COVID-19. 319 children met the criteria of a suspected case. COVID-19 was diagnosed in 15/319 (4.7%) patients (8 male; mean age 10.5 years). All of them had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 17 publications
(36 reference statements)
0
39
0
Order By: Relevance
“…In adults with COVID-19, it has been observed that independent risk factors associated with mortality included older age, male sex, high fraction of inspired oxygen, high positive end-expiratory pressure, and history of chronic obstructive pulmonary disease, hypercholesterolemia, and type 2 diabetes [9,10]. Studies that have evaluated which factors could predict severe pediatric COVID-19 have shown that younger age, pre-existing underlying chronic severe comorbidities, male sex and lower respiratory tract infection signs and symptoms at presentation could be considered risk factors for PICU admission [11][12][13]. Among laboratory markers, increased leukocyte count, lymphopenia, and elevated inflammatory markers (C-reactive protein and procalcitonin) were those more frequently associated with PICU admission [11][12][13].…”
Section: Risk Factors Associated With Severe Outcome Among Pediatric Patients With Covid-19mentioning
confidence: 99%
See 4 more Smart Citations
“…In adults with COVID-19, it has been observed that independent risk factors associated with mortality included older age, male sex, high fraction of inspired oxygen, high positive end-expiratory pressure, and history of chronic obstructive pulmonary disease, hypercholesterolemia, and type 2 diabetes [9,10]. Studies that have evaluated which factors could predict severe pediatric COVID-19 have shown that younger age, pre-existing underlying chronic severe comorbidities, male sex and lower respiratory tract infection signs and symptoms at presentation could be considered risk factors for PICU admission [11][12][13]. Among laboratory markers, increased leukocyte count, lymphopenia, and elevated inflammatory markers (C-reactive protein and procalcitonin) were those more frequently associated with PICU admission [11][12][13].…”
Section: Risk Factors Associated With Severe Outcome Among Pediatric Patients With Covid-19mentioning
confidence: 99%
“…Studies that have evaluated which factors could predict severe pediatric COVID-19 have shown that younger age, pre-existing underlying chronic severe comorbidities, male sex and lower respiratory tract infection signs and symptoms at presentation could be considered risk factors for PICU admission [11][12][13]. Among laboratory markers, increased leukocyte count, lymphopenia, and elevated inflammatory markers (C-reactive protein and procalcitonin) were those more frequently associated with PICU admission [11][12][13]. Only in some cases were lactate dehydrogenase, pro-B-type natriuretic peptide and troponin studied and found to be increased, suggesting a potential role of these variables as markers of risk.…”
Section: Risk Factors Associated With Severe Outcome Among Pediatric Patients With Covid-19mentioning
confidence: 99%
See 3 more Smart Citations